(untitled) (Journal of Humanities and Social Sciences Research, 2023)
As a process of extending possibilities for people, the notion of sustainable development is regarded internationally as one of the approaches to address challenges. As a result, the current study is important in examining the extent to which some of the goals of sustainable development are met in the primary stage physical education lesson from the perspective of teachers in Babil Governorate through advanced curricula that keep up with the demands of sustainable development, which aims to develop physical education lessons for the primary stage. Concerning the research topic, the researchers discovered that the aims of sustainable development linked with educational curriculum, particularly the primary stage physical education lesson, did not attain the needed level to meet its varied purposes. As a consequence, the two researchers agreed to conduct an analytical investigation of the extent to which some sustainable development goals were met in the primary stage physical education lesson from the teachers’ perspective. The research sought to identify some of the aims of sustainable development linked with the primary stage physical education lesson. The descriptive technique was chosen by the researchers in survey studies since it was suited to the nature of the research topic. The research community included (685) physical education instructors from the General Directorate of Education of Babylon Governorate and its divisions, who were distributed over (5) regions of the province of Babylon. In terms of the essential findings, sustainable development is the pioneer in implementing the requirements of the primary stage physical education lesson. The most significant recommendation is: Incorporate certain sustainable development goals into instructional methods in physical education lessons.